Biodegradation of 2t engine oil by brevibacillus agri strain Isolated from petroleum contaminated soil (Funded Work) - SHIVENDRA SHARMA; HARDIK PATHAK (International Journal of Pharma and Bio Sciences, 2017)
Petroleum has been used for many decades for illumination and, on a smaller scale, as lubricant. Environmental pollution by petroleum hydrocarbons has become a serious problem all around the world. The contaminations caused by petrol and petroleum products have been proved a great disaster on ecosystem. Bioremediation is one of the economical methods used to treat this threat and an approach to save the environment from petroleum related issues. This study was aimed to determine the degradation potential of Brevibacillus agri strain isolated from petroleum contaminated soil which was collected from arid region of Rajasthan (Churu). Enrichment culture technique was used for isolation and some biochemical tests were performed at laboratory scale. Bacterial cell density was monitored by measuring the OD at 620nm. This culture could utilize engine oil as sole carbon and energy source in aerobic conditions, highest 59% degradation of 2T engine oil was observed after 28 days. Gravimetric analysis method and GC-MS were used to determine the biodegradation of 2T engine oil with the aromatic and aliphatic fractions. Identification and characterization of isolated bacterial strain biochemical, morphological characterization and 16s sequencing technique were performed. Brevibacillus agri has good potential for decontamination of oil contaminated soil in the environment.